Give Me Life : Iconography and Identity in East LA Murals - Barnet-Sánchez, Holly; Drescher, Tim (Book collections on Project MUSE., 2016)
This book offers detailed analyses of individual East LA murals, sets them in social context, and explains how they were produced.